2020
DOI: 10.1186/s12889-020-08495-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening and care for alcohol use disorder in France: expectations, barriers and levers using a mixed-methods approach

Abstract: Background:The widespread under-screening and under-treatment of alcohol use disorder (AUD) contributes to its health and socioeconomic burden. We conducted a mixed-methods (qualitative and qualitative) study in people with alcohol use disorder (PWAUD) to explore their expectations, as well as barriers and levers to AUD care.Methods: Individuals with AUDIT > 15 (N = 179) were interviewed using computer-assisted interviews in several medical and non-medical sites (e.g., bars) (quantitative substudy). We also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…From the patient perspective, the absence of simplified guidance adds to the feeling of discrimination and the complexity of the health-care pathways as main barriers to engagement in liver disease care. 323 In one qualitative study, the presence of national guidelines, combined with clear flowcharts or computer prompts, increased the confidence of primary care workers in their diagnostic capabilities. 324 The issue of end-of-life care in advanced liver disease is an area within which much can be improved.…”
Section: Tablementioning
confidence: 99%
“…From the patient perspective, the absence of simplified guidance adds to the feeling of discrimination and the complexity of the health-care pathways as main barriers to engagement in liver disease care. 323 In one qualitative study, the presence of national guidelines, combined with clear flowcharts or computer prompts, increased the confidence of primary care workers in their diagnostic capabilities. 324 The issue of end-of-life care in advanced liver disease is an area within which much can be improved.…”
Section: Tablementioning
confidence: 99%
“…Perceived lack of need, competing priorities (e.g. avoiding opioid withdrawal), discrimination, stigma and difficulty in navigating health systems are reasons that PWID and people with alcohol use disorder may avoid seeking care ( Motavalli et al, 2021 ; Zewdu et al, 2019 ; Costa et al, 2020 ). Inadequate funding for harm reduction and addiction programmes is a barrier to HBV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The standard unit (US) of alcohol consumption is also controversial, especially in relation to the country/culture in which the research is carried out: in France -contains 10 g of pure alcohol, as explained by Costa et al (2020) Carney et al found in a study published in 2019 on 662 active HIV-infected soldiers in the United States that consumption of alcohol is a high-risk factor for respondents with recent onset of depressive symptoms. They concluded that there is a linear relationship between daily alcohol consumption and the increased risk of engaging in harmful sexual behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Like sexual activity, risky sex is defined in several forms: sexual intercourse with two or more partners in the last 12 McDougall and colleagues (2019) associating risky sex with psychological characteristics found that 6.8% of study participants, female students under 30, were victims of unconsented sex during university courses. Moreover, they were 2.1 times more likely to be at risk of depression than those who had not experienced sexual victimization.…”
Section: Resultsmentioning
confidence: 99%